2003
DOI: 10.1159/000070946
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Skin Manifestation of Cutaneous Amyloidosis

Abstract: A 76-year-old man with a 20-year history of extensive cutaneous amyloidosis is reported. He had asymptomatic symmetric brownish reticulated pigmented patches with well-demarcated borders on his thighs, lower legs, dorsal feet and both arms. The trunk and popliteal fossae were not affected. A skin biopsy specimen showed abundant amyloid deposits in the papillary dermis and reticular dermis. Despite the extensive cutaneous involvement and large amount of amyloid in the deep dermis, no evidence of systemic amyloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…[6], [7], [10] In the present study, out of 39 (78%) patients of frictional melanosis, 79.48% showed involvement of extensor aspect of arm followed by extensor aspect of forearm (69.23%) and interscapular area (41.02%) which is consistent with other studies. [14], [15] In our study, out of 11 (22%) patients of macular amyloidosis, 100% showed involvement of extensor aspect of forearms which is in contrast to one study done in Washington, DC where in lower extremities are found to be common location for macular amyloidosis. [12] In the present study, hyperpigmentation in ripple pattern was the commonest morphological lesion which is consistent with other studies.…”
Section: Discussioncontrasting
confidence: 80%
“…[6], [7], [10] In the present study, out of 39 (78%) patients of frictional melanosis, 79.48% showed involvement of extensor aspect of arm followed by extensor aspect of forearm (69.23%) and interscapular area (41.02%) which is consistent with other studies. [14], [15] In our study, out of 11 (22%) patients of macular amyloidosis, 100% showed involvement of extensor aspect of forearms which is in contrast to one study done in Washington, DC where in lower extremities are found to be common location for macular amyloidosis. [12] In the present study, hyperpigmentation in ripple pattern was the commonest morphological lesion which is consistent with other studies.…”
Section: Discussioncontrasting
confidence: 80%
“…Amyloidosis is a term that describes a group of disorders characterized by the abnormal deposition of proteins causing alterations of tissue architecture and function 1 . Amyloid may be deposited throughout many organs of the body as in systemic amyloidosis, or it may be restricted to a single tissue site as in localized amyloidosis 2 . Nodular localized primary cutaneous amyloidosis (NLPCA) is the rarest variant of cutaneous amyloidoses 3 …”
Section: Introductionmentioning
confidence: 99%
“…1 Amyloid may be deposited throughout many organs of the body as in systemic amyloidosis, or it may be restricted to a single tissue site as in localized amyloidosis. 2 Nodular localized primary cutaneous amyloidosis (NLPCA) is the rarest variant of cutaneous amyloidoses. 3 Primary cutaneous marginal zone B-cell lymphoma (PCMZL) is a low-grade malignant B-cell lymphoma of the skin, and it is considered part of the broad group of extranodal marginal zone B-cell lymphomas (EMZL) commonly involving mucosal sites, called MALT (mucosa-associated lymphoid tissue) lymphomas.…”
Section: Introductionmentioning
confidence: 99%